Accountability and Incentives of Appointed and Elected Public Officials - Hessami, Zohal (The Review of Economics and Statistics, 2018)
Political agency models suggest that elected public officials choose different policies than appointed officials do. This paper is the first (a) to apply a clean empirical design to study whether the selection rule has a causal effect on public officials’ policy choices and (b) to investigate transmission channels. I exploit a unique setting in Germany, where a reform has created quasi-experimental variation in the selection rule for mayors. As the outcome variable, I use data on grant receipts for highly visible investment projects for which mayors must apply to the state government. Elected mayors attract 7% to 7.4% more grants in election years; for appointed mayors, there is no cycle. Using hand-collected data on mayor characteristics, I find suggestive evidence that although the selection of mayors changes following the reform studied, a likely reason for the observed cycle is that elected mayors have stronger electoral incentives.